Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 10, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 10, 1930. By great good fortune last Monday night, we accepted the kind invitation of a friend and went down to the auditorium of the Unitarian church on Pearl Street to hear and see the entertainment provided in connection with a meeting of the Hartford Fish and Game club. A principal feature of the entertainment was an address by Dr. John Warren Harper on his angling experiences in various parts of the world, especially New Zealand.
1 electronic record. Scanned newspaper article. 2 image scans. 1.39 MB (1,461,914 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 29.2 MB (30,669,030 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers